Clinical experience with Clonidine in the treatment of hypertension - Ahmad H. Asdie, Ahmad H. Asdie (Universitas Gadjah Mada, 1981)
In this article we reported our experience with Clonidine in treating hypertensive patients in the Department of Internal Medicine, Gadjah Mada University Hospital, Pugeran, Yogyakarta. 25 patients suffering from severe or moderate hypertension of 13 females and 10 males were included in the study. The treatment began with a small dose of 0.075 mg bid. This dose if necessary was increased every 3-7 days. In some patients diuretics were added.Side effects and effect of treatment on the blood pressure are described and discussed.Key Words: hypertension - clooidine - diuretics - renal failure - antihypertensive drugs